Development of Problem-Based Learning LKPD Based Local Potential of Baros Mangroves in Biology Subjects Environmental Pollution Material - Novitha; Suhartini (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to Producing learning media the PBL modeled LKPD based on the local potential of Mangrove Baros on environmental pollution material is suitable, practical and effective in enhancing the problem-solving abilities and environmental care attitudes of students in class X at SMAN 1 Kretek, Bantul, Yogyakarta. This research follows a research and development approach using the Four-D (4D) model, which consists of four stages: Define, Design, Develop, and Disseminate. Field trials of the LKPD PBL based on the local mangrove potential in Baros for environmental pollution materials were conducted through quasi-experimental research with a pretest-posttest control group design. The subjects of the field trial were 60 students from two classes. Data collection involved problem-solving ability test questions and questionnaires on environmental care attitudes. Data analysis was performed using the MANOVA test to analyze differences in students' problem-solving abilities and environmental care attitudes. The results of the MANOVA test indicated differences in the use of PBL modeled LKPD based on the local mangrove potential in Baros for environmental pollution materials concerning problem-solving abilities and environmental care attitudes.